The effect of isotonic drink on heart rates recovery after pencak silat activity: a study on female students in an islamic boarding school - Hadjarati, Hartono; Massa, Resa Sukardi (Jurnal Keolahragaan, 2023)
The aim of this study was to examine the effect of isotonic drinks on students' heart rates. This experimental research relied on a randomized pretest–posttest control group design; it consisted of one control group (t1) and one treatment group (t2). All participants were treated with the same exercise protocol including endurance training specifically for the branches of pencak silat (exercise straight kick techniques, scythe while hitting). The control group consumed mineral water, while the treatment group was provided with an isotonic drink after exercise. Following the treatment phase was the calculation of participants' heart rates for one minute; this process was replicated three times: before the exercise (T1), 60 to 90 minutes after the exercises (T2), and 10 minutes after the exercise interval (T3). All data were analyzed using a T-test. The results revealed that the initial heart rates of the control and treatment groups were 72.6 ± 10.36 and 66.3 ± 8.60, respectively.  In other words, there were no differences between the two groups. The initial heart rates of the control group control and treatment group after the exercise was 159.2 ± 10.48 and 149.0 ± 8.59, respectively. According to the t-test results, there was a difference (p < 0.05) in the heart rates of the control group and treatment group after the exercises. The initial heart rates of the control group control and treatment group after the exercise interval was 76.2 ± 11.0 and 65.9 ± 8.62, respectively. The t-test results reported a difference (p < 0.05) in the heart rates of the control group and treatment group after the exercise interval of 10 minutes. Isotonic drinks significantly to heart rates recovery after pencak silat exercise of female students.